Peningkatan Hasil Belajar IPA melalui Model Pembelajaran Project Based Learning (PjBL) Pada Siswa Kelas V SDN 50 Cakranegara Tahun Ajaran 2022/2023 - Rahmatiya, Ita; Arjudin, Arjudin; Kaninta, Novianti (Journal of Science Instruction and Technology, 2023)
This study aims to determine the improvement of science learning outcomes through the Project Based Learning model in grade V students of SDN 50 Cakranegara for the 2022/2023 school year. The implementation of learning is carried out as many as 2 cycles, then after learning evaluation activities are carried out by completing test questions to test the absorption of learning material and learning outcomes obtained by students in each cycle. The stages of implementation of each cycle are planning, acting, observing, and reflecting. The Project Based Learning model has steps to use it, namely orienting students to problems, organizing learning planning, preparing project creation schedules, presenting and developing work, analysis and evaluation of student work. Overall, the learning process has increased from each cycle, where at the pre-action stage with the average value of science learning outcomes of grade V students under KKM is 64.09 with the completeness of learning outcomes as many as 15 students. Increased in the first cycle with the average value of science learning outcomes obtained by students which was 72.57 with the completeness of learning outcomes as many as 23 students with a percentage of 65.69% and increased again in the second cycle to 80.00 with the completeness of learning outcomes as many as 28 students with a percentage of 84.84%, meaning that the learning process carried out for science learning outcomes through the project based learning model in grade V students of SDN 50 Cakranegara in 2022/2023 experienced Increased.